Recent Developments in Time-Frequency Analysis 1998
DOI: 10.1007/978-1-4757-2838-5_3
|View full text |Cite
|
Sign up to set email alerts
|

On the Statistics of Spectrogram Reassignment Vectors

Abstract: Abstract. Reassignment is a non-linear technique which can improve on the localization of a spectrogram by moving its values according to a suitable vector field. Statistical properties of spectrogram reassignment vectors are investigated in detail. Closed form expressions are given when the observation consists in a non-random component embedded in white Gaussian circular noise, and when the analysis window is Gaussian. An extension to arbitrary windows is also proposed and theoretical claims are supported by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Another important topic in the study of SSTs is the statistical analysis of the synchrosqueezing operator, since noise is ubiquitous in real applications. A pioneer paper [10] in this direction studied the statistical properties of the 1D spectrogram reassignment method by calculating the probability density function of white Gaussian noise after reassignment. A recent paper [36] focused on the statistical analysis of the 1D SSWT for white Gaussian noise.…”
Section: Introductionmentioning
confidence: 99%
“…Another important topic in the study of SSTs is the statistical analysis of the synchrosqueezing operator, since noise is ubiquitous in real applications. A pioneer paper [10] in this direction studied the statistical properties of the 1D spectrogram reassignment method by calculating the probability density function of white Gaussian noise after reassignment. A recent paper [36] focused on the statistical analysis of the 1D SSWT for white Gaussian noise.…”
Section: Introductionmentioning
confidence: 99%
“…Some interesting results for the phase derivative have been shown in the context of reassignment. In [8], the following result is given: We consider a zero-mean Gaussian analytic white noise f such that…”
Section: Numerical Observationsmentioning
confidence: 99%
“…[4] showed that some Cohen's group TFRs can be used to implement optimal linear detection, by providing an equivalent implementation of the time domain matched filter in the time frequency domain. This seminal work was followed by a number of studies about time-frequency detection / classification of signals, see e.g., [5]- [8]. All these approaches rely on the idea that the noise is spread all over the timefrequency plane, thus increasing the local signal-to-noise ratio.…”
Section: Introduction a Backgroundmentioning
confidence: 99%